STATE SECURITY AND HUMAN SECURITY IN BORDER MANAGEMENT - Rohilie, Haunan Fachry (Universitas Jenderal Ahmad Yani, 2020)
This study tries to see how the condition borders region between Indonesia and Malaysia, in Ketungau Hulu subdistrict. Analysis is conducted to see how the borders management in Indonesia with two approaches. The first approach is the analysis of State Security used to see how the treatment of the state to maintain state sovereignty from the external threats that dominated by military. The second approach is the analysis of Human Security which is more emphasis on the security of citizens as seen from the fulfillment of basic human needs, both in terms of welfare, education, health, and so forth.